Designing Virtual Reality Learning Media To Enrich Early Childhood Learning On Underwater Ecosystems - Rahma, Adelia; Syakira, Fadya; Alpita, Nur; Kiromiyah, Zulfatul; Anesty Mashudi , Esya (Seulanga : Jurnal Pendidikan Anak, 2024)
Indonesia is an archipelago with abundant and beautiful marine resources. This is due to the underwater ecosystem that is still maintained. In order to maintain the underwater ecosystem, it is important to instil awareness to protect the environment from an early age from things that can damage the underwater ecosystem. Therefore, it is important for children to understand the underwater situation so that children know how beautiful and rich in benefits to be enjoyed by the Indonesian people. This makes learning about underwater life necessary for early childhood to enrich their knowledge and understanding. Children cannot yet be invited to think abstractly, so the use of concrete media in order to be able to channel children's imagination into more real things. The learning media used to study underwater ecosystems mostly only use two-dimensional visual media, so children do not feel the real sensation of being under the sea. Therefore, this research aims to develop two-dimensional visual media into virtual reality media. The existence of Virtual Reality learning media is able to provide real information and can interact directly with the marine environment. This research uses design research methods with qualitative analysis that discusses how to design Virtual Reality applications suitable for children aged 5-6 years that can simulate underwater ecosystems. Virtual Reality which is used as an alternative media in learning about marine biota for children is an effort to preserve marine biota in Indonesia.